Keeping the city going - Floca, Brian (New York : Atheneum Books for Young Readers, 2021)
An ode to the essential workers keeping the country operating during the Covid-19 pandemic.
Booklist starred, April 2021
Pub Weekly, March 2021
Kirkus Starred, March 2021
Horn Book, March 2021
Bulletin (Center for Children's Books), April 2021
K-3
Keywords: Community life -- Juvenile fiction; Occupations -- Juvenile fiction; City and town life -- Juvenile fiction; Quarantine -- Juvenile fiction; COVID-19 (Disease) -- Juvenile fiction; Community life -- Fiction; Occupations -- Fiction; City and town life -- Fiction; Quarantine -- Fiction; COVID-19 (Disease) -- Fiction